PENGARUH LABELISASI HARGA TERHADAP KEPUTUSAN KONSUMEN DALAM PEMBELIAN PRODUK BERDASARKAN UNDANG-UNDANG PERLINDUNGAN KONSUMEN - Swandewi, Luh De; Sawitri, Dewa Ayu Dian (Kertha Negara : Journal Ilmu Hukum, 2023)
Price labeling is a description or information that can be in the form of writing, pictures, or a combination of both which is located on one part of the product which contains information on the value of the item or product. Price labeling can determine the class of an item or product, as a means of communication between business actors and consumers things consumers need to know about about an item or product, provide a sense of security for consumers because the price is clearly listed, and is a guide for consumers whether the price listed is in accordance with the function and quality of an item or product. This research aims to know the existence of the price tag in buying and selling activities and the effect of price labeling on consumers. The research method used is Empirical research methods which is based on the results of interviews and direct observation. Price labeling provide convenience for consumers as well as business actors. Consumers will no longer ask about prices and business actors do not check prices one by one anymore in the amount of goods or products that are not small.